Pazos Alonso, C. (2022). Francisca Wood and Nineteenth-Century Periodical Culture: Pressing for Change. Cambridge: Legenda (Studies in Hispanic and Lusophone Cultures, 35), 250 pp. ISBN 978–1–78188–799–8. - Ducatteau, Héloïse Elisabeth Marie-Vincent Ghislaine (Journal of Sociology: Bulletin of Yerevan University, 2024)
book review